Development and validation of a factor analysis-validated comprehensive scale for measuring innovative work behavior - Kanakarn Phanniphong; Khahan Na-Nan (Sustainable Futures)
This research aimed to develop and validate a scale for measuring innovative work behavior (IWB) among operational-level employees in the multinational beverage manufacturing industry. The study population consisted of 200 employees from multinational beverage manufacturers in Thailand. Methods included confirmatory factor analysis (CFA), composite reliability (CR), and mean variance (AVE). The scale exhibited excellent internal consistency, with a composite reliability (CR) coefficient of 0.94 and an average variance extracted (AVE) of 0.85. The validated scale can be used to measure employees' innovative work behavior and serve as a research instrument for investigating innovative work behavior issues. This study contributes to the body of knowledge by creating a self-assessment scale for innovative work behavior among operational-level employees in the multinational beverage manufacturing industry. The scale can be utilized by management to enhance organizational efficiency and effectiveness.